Financing social protection - Cichon, Michael; Scholz, Wolfgang; Van de Meerendonk, Arthur; Hagemejer, Krzysztof; Bertranou, Fabio; Plamondon, Pierre (Geneva, 2004)
"Designing social protection systems that are effective and equitable as well as fiscally, financially and economically efficient has been a challenge for many countries. Offers a comprehensive overview of the many financing options available while also provides a thorough analysis of their advantages and disadvantages and their financial and economic implications. The most important task of social protection systems is to alleviate and prevent poverty. The book presents a "methodological toolbox" from which social protection planners, managers and social policy analysts can work."